Apical hypertrophic cardiomyopathy with preexcitation presenting as a myocardial infarction and ischemic stroke with a history of recurrent syncope: A case report. Issue 4 (14th March 2019) - Al‐Saadi, Jonathan; Mattsson, Gustav; Kader, Rozh; Magnusson, Peter
Key Clinical Message: Contrast‐enhanced echocardiography or cardiac magnetic resonance imaging is of value in the diagnosis of apical hypertrophic cardiomyopathy. Apical hypertrophic cardiomyopathy is rare in Caucasians, and gene negativity does not rule out the diagnosis. Risk stratification for sudden cardiac death and decisions about anticoagulation in cases with atrial fibrillation should be based on guidelines. Abstract : Contrast‐enhanced echocardiography or cardiac magnetic resonance imaging is of value in the diagnosis of apical hypertrophic cardiomyopathy. Apical hypertrophic cardiomyopathy is rare in Caucasians, and gene negativity does not rule out the diagnosis. Risk stratification for sudden cardiac death and decisions about anticoagulation in cases with atrial fibrillation should be based on guidelines.